2006 IEEE Sarnoff Symposium 2006
DOI: 10.1109/sarnof.2006.4534723
|View full text |Cite
|
Sign up to set email alerts
|

Potential for Intra-Vehicle Wireless Automotive Sensor Networks

Abstract: We propose using a wireless network to facilitate communications between sensors/switches and control units located within a vehicle. In a typical modern vehicle, the most demanding sensor will require a latency of approximately less than 1 msec with throughput of 12 kbps. Further, the network will need to support about 15 sensors with this requirement. The least demanding sensor will require a latency of approximately 50 msec with data throughput rate of 5 bps and will need to support about 20 of these types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 4 publications
0
34
0
2
Order By: Relevance
“…An early analysis was carried out in [2] where latency for the IEEE 802.15.4 family of protocols for low-rate wireless personal area networks (LR-WPAN) depending on network configuration and topology was performed. An ample review was done in [3] for general wired and wireless communication in car sensor networks and the potential for low-rate low-power protocols like Bluetooth, ZigBee, etc. in various applications was underlined and the conclusion was drawn that as well as in other domains, there persists a strong need for standardization in the field enabling wider adoption of such technologies.…”
Section: Introductionmentioning
confidence: 99%
“…An early analysis was carried out in [2] where latency for the IEEE 802.15.4 family of protocols for low-rate wireless personal area networks (LR-WPAN) depending on network configuration and topology was performed. An ample review was done in [3] for general wired and wireless communication in car sensor networks and the potential for low-rate low-power protocols like Bluetooth, ZigBee, etc. in various applications was underlined and the conclusion was drawn that as well as in other domains, there persists a strong need for standardization in the field enabling wider adoption of such technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Example applications include: health care and elderly care [3], security (policemen, firemen etc. ), industrial application, as shown by Karnouskos et al [4], vehicle testing [5] and winter road conditioning [6]. Typical requirements for these types of applications ranges from a few data transmissions per hour (posture, position, temperature etc) to continuues data transmission with sample rates of several kHz (vibration, audio, CAN-bus, etc).…”
Section: Introductionmentioning
confidence: 99%
“…Wireless intra-vehicle communications system has been proposed as a new type of communications system that can provide onboard passengers with bidirectional highspeed data exchange services for both communications and entertainment [2,3]. For the purpose of safety, comfort and convenience, WSNs are being deployed in the new models of automotives to collect such information as temperature, speed, pressure, and so on.…”
Section: Introductionmentioning
confidence: 99%